1990
DOI: 10.1159/000205050
|View full text |Cite
|
Sign up to set email alerts
|

Compound Heterozygosity for a Mild β<sup>+</sup> and a Rare β°-Thalassemia Allele

Abstract: Hematological and hemoglobin composition data are presented for 14 members of a Surinam family (and for 1 unrelated subject) with either a β-thalassemia heterozygosity [5 with the -29 (A – G) β+ mutation and 5 with the IVS II-849 (A→G) β° mutation] or a compound heterozygosity (the 5 remaining patients). Identification of the mutation was by hybridization of amplified DNA with 32P-labelled synthetic oligonucleotides. The data indicate distinct differences between the two groups of heteroz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This mutation is reported in American Black families and families from Surinam, Guadeloupe [4][5][6][7]. Here, we report clinical findings of compound heterozygosity of this splice site mutation (i.e., IVS2.849 A-G) and another splice site mutation IVS1.1 A-G.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…This mutation is reported in American Black families and families from Surinam, Guadeloupe [4][5][6][7]. Here, we report clinical findings of compound heterozygosity of this splice site mutation (i.e., IVS2.849 A-G) and another splice site mutation IVS1.1 A-G.…”
mentioning
confidence: 60%
“…Athweh et al performed functional analysis of this mutant gene obtained from a Black patient, and showed that the mutation inactivated normal acceptor splice site and resulted in some utilization of a cryptic splice site near position 580 of IVS2 [5]. This mutation was later described in a Surinam Creole family [6]. Lastly, Romana et al have found this mutation in 2 families from Guadeloupe, which is an island in the Caribbean with a population admixture of West African, Asian Indian, and Caucasian ancestry [7].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, unusual genetic combinations involving certain genetic defects that are generally prevalent in South‐East Asia are seen in this population. The presence of −SEA deletion causing Hb H disease (Giordano et al , 1997) and the presence of the −29 (A→G) β ‐thalassaemia mutation (Codrington et al , 1990), which are present in the Chinese population, are some examples. It is conjectured that the codon 47 (+A) mutation must have migrated to Suriname about 200–300 years ago during the slave trade.…”
mentioning
confidence: 99%